2019
DOI: 10.1002/slct.201900732
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Transfer Process of Bismuth Vanadate Interleaved Graphitic Carbon Nitride Nanohybrids in Mediator‐Free Direct Z Scheme Photoelectrocatalytic Water Splitting

Abstract: In the present work, graphitic carbon nitride‐bismuth vanadate (g‐C3N4‐BiVO4) nanohybrid materials with different wt. % of g‐C3N4 were successfully synthesized by a simple hydrothermal method and characterized by UV‐Visible diffuse reflectance spectroscopy (DRS), photoluminescence spectroscopy (PLS), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), Fourier‐transform infrared spectroscopy (FT‐IR), field emission scanning electron microscopy (FE‐SEM), energy dispersive X‐ray (EDAX) absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…The prominent negative shift of flat band potential for BiVO 4 /GCN photoanode is related to the favorable band gap (BiVO 4 ∼ 2.46 eV and GCN ∼ 2.7 eV) and conduction band position (BiVO 4 ∼ 0.249 V RHE and GCN = ca. −1.17 V RHE ) . This will lead to the formation of the band bending at the nanojunction between GCN and BiVO 4 , which ultimately help in efficient charge transfer with minimizing the recombination losses of charge carriers responsible for water oxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The prominent negative shift of flat band potential for BiVO 4 /GCN photoanode is related to the favorable band gap (BiVO 4 ∼ 2.46 eV and GCN ∼ 2.7 eV) and conduction band position (BiVO 4 ∼ 0.249 V RHE and GCN = ca. −1.17 V RHE ) . This will lead to the formation of the band bending at the nanojunction between GCN and BiVO 4 , which ultimately help in efficient charge transfer with minimizing the recombination losses of charge carriers responsible for water oxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several carbon-based materials such as graphene oxide (GO), carbon nanofibers (CNFs), carbon nanotubes (CNTs), ordered mesoporous carbon (OMC), and graphitic carbon nitride (GCN) have been used for electrochemical sensors. Among them, GCN received a lot of attention due to its unique structural characteristics, large surface area, high electrical conductivity, high mechanical strength, and chemical stability. In addition, many researchers have reported that heteroatom (S, N, P) doping in the GCN framework is an excellent strategy for improving its activity more effectively for various electrochemical applications, including sensing, photocatalytic degradation, and water catalysis. Through this, MoN’s stability and electrical conductivity can be enhanced by forming a composite material with heteroatom-doped GCN. As a result, the combination of MoN and heteroatom-doped GCN is expected to significantly enhance the activity of the electrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FT-IR) spectra were recorded to reveal the interfacial interactions. Figure f depicts the symmetric stretching vibrations of the VO 4 unit on pristine BVNS from 600 to 800 cm –1 , and no obvious change is seen after Au modification. Besides, the additional peaks at 1058, 1114, 1291, 1330, and 1412 cm –1 appear in 3CuPc/BVNS, which are ascribed to phthalocyanine skeletal and center metal–ligand vibrations, respectively .…”
Section: Resultsmentioning
confidence: 99%